Development and validation of an LC-MS/MS method for determination of 8-iso-prostaglandin F2 alpha in human saliva: LC-MS/MS METHOD FOR 8-isoPGF2α DETERMINATION IN SALIVA - Tomova, Zlatina; Tomov, Desislav; Vlahova, Angelina; Chaova-Gizdakova, Veneta; Yoanidu, Lyubka; Svinarov, Dobrin (Journal of Medical Biochemistry, 2022)
Background. Increased formation of reactive oxygen species may be caused by the ion release of the metal alloys used in prosthetic dental restorations due to corrosion process. Isoprostanes, as products of lipid peroxidation, can be used as a marker for oxidative stress in the body. There are two big advantages of using isoprostanes as oxidative stress marker – presence in all fluids in the body and low reactivity. Saliva provides non-invasive, painless, and cost-effective sample collection and can be used as an alternative testing medium of blood and urine. Methods. This study presents the development and validation of a sample LC-MS/MS method for quantification of 8-isoprostaglandin F2-α in human saliva using salt-out assisted liquid-liquid extraction (SALLE). Results. The selected sample preparation procedure optimized chromatographic separation and mass detection provided high recovery and sensitivity of the analysis. The calibration curve was obtained in the predefined range 25 – 329 ng/L with R2 larger than 0.995. Normalized matrix varied between 89.7 % and 113.5%. The method showed sufficient accuracy and precision - accuracy in the range 89.7 % – 113.9 %, and precision between 2.3% and 5.4%. Conclusion. The proposed method is validated according to current EMA/FDA industrial guidance for bioanalysis and offers an appropriate level of sensitivity as well as sufficient accuracy and precision.